Investigation of Acute Toxicity Level of Gongronema latifolium Leaf Extract on White Albino Rat (IPS Journal of Toxicology, 2025)
The aim of this study is to investigate the level of toxicity in Gongronema latifolium leaf extract on male swiss albino rats. Lorke’s method of toxicity was used in this research study. The experimental animals were administered with different doses of the extract. The rats were monitored closely for behavioural changes, difficulty in breathing and death for the period of two weeks. At the end of the two weeks study, all the animals used for the experiment were sacrificed and the internal organ-body weight ratio (OBR) were determined and compared with the values from the control group. The LD50 was found to be >5000 mg/kg body weight. There was no significant weight decrease (P>0.05) among dose groups of up to 1000mg/kg body weight. Liver congestion was observed with 100mg/kg body weight dose group. The OBR mean values for kidney, liver, and heart were not significantly (P>0.05) different from that of the control group. The extract therefore is safe for human consumption.
Keywords: Acute toxicity; Gongronema latifolium; Albino Rats; Traditional Medicine